1998
DOI: 10.1074/jbc.273.12.6689
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Prostaglandin E2 Transport across the Plasma Membrane of HeLa Cells and Xenopus Oocytes Expressing the Prostaglandin Transporter “PGT”

Abstract: We recently identified a novel prostaglandin transporter called PGT (Kanai, N., Lu, R., Satriano, J. A., Bao, Y., Wolkoff, A. W., and Schuster, V. L. (1995) Science 268, 866 -869). Based on initial functional studies, we have hypothesized that PGT might mediate the release of newly synthesized prostaglandins (PG), epithelial transport of PGs, or metabolic clearance of PGs. Here we examined the mechanism of PGT transport as expressed in HeLa cells and Xenopus oocytes, using isotopic PG influx and efflux studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
101
0
3

Year Published

1998
1998
2011
2011

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(113 citation statements)
references
References 32 publications
(39 reference statements)
9
101
0
3
Order By: Relevance
“…Other observations support this picture: In monolayers of cultured canine cortical collecting tubule cells, for example, PGE 2 crossed the monolayer slowly, at the same rate as the inulin used to measure imperfections in the monolayer (41). Similarly, human cell lines (32,42) and MDCKII cells (43) were impermeable to prostanoids, with no accumulation (or flux) of prostaglandins or thromboxane unless PGT was heterologously expressed. The permeability of Xenopus laevis oocytes, a model system used in many studies of transport proteins, is also low for prostaglandins (32,36,42).…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Other observations support this picture: In monolayers of cultured canine cortical collecting tubule cells, for example, PGE 2 crossed the monolayer slowly, at the same rate as the inulin used to measure imperfections in the monolayer (41). Similarly, human cell lines (32,42) and MDCKII cells (43) were impermeable to prostanoids, with no accumulation (or flux) of prostaglandins or thromboxane unless PGT was heterologously expressed. The permeability of Xenopus laevis oocytes, a model system used in many studies of transport proteins, is also low for prostaglandins (32,36,42).…”
Section: Discussionsupporting
confidence: 55%
“…Similarly, human cell lines (32,42) and MDCKII cells (43) were impermeable to prostanoids, with no accumulation (or flux) of prostaglandins or thromboxane unless PGT was heterologously expressed. The permeability of Xenopus laevis oocytes, a model system used in many studies of transport proteins, is also low for prostaglandins (32,36,42). Despite this low intrinsic permeability, the amount of label released from oocytes injected with [ 3 H]PGE 2 increased linearly with concentration, up to an intraoocyte concentration of 380 nM, suggestive of passive diffusion (42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the renal collecting duct expresses apical EP 4 receptors and basolateral EP 1 receptors that signal opposite effects on Na ϩ and water transport (4,5). Since PGE2 likely exits collecting duct cells non-directionally by simple diffusion (37,38), one method for directing PGE2 toward basolateral (EP 1 ) receptors would be to use an apical reuptake carrier like PGT. The reclaimed PGE2 could either be oxidized or could rediffuse intact out of the cell across the basolateral membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular PGs exert their major actions via multiple cell surface G-protein coupled receptors (Coleman et al, 1994;Narumiya et al, 1999) and are immediately taken up intracellularly for their inactivation or action via specific nuclear receptors (Zhu et al, 2006). Prostanglandin transport takes place via a prostaglandin transporter (PGT) and this transport plays an important role since, at physiologic pH, PGs exist as charged anions and diffuse poorly across the plasma membrane (Schuster, 1998;Chan et al, 1998). PGT has been identified in various tissues (endothelial cells, liver, kidney, lung, smooth muscle) (Lu et al, 1996) and, in contrast to multiple PG specific receptors and their isoforms (Narumiya et al, 1999), PGT has been shown to have affinity with most major PGs (PGE 2 =PGF 2 >PGD 2 ) (Schuster, 1998).…”
Section: Introductionmentioning
confidence: 99%